Phase Transformations and Shape Memory Behavior in Ni3Ta-based Intermetallics. (2015) - Kosorukova, T.A.; Firstov, G.S.; Koval, Yu.N.; Van Humbeeck, J.; Zhuravlev, B.
Abstract: Stoichiometric Ni3 Ta intermetallic compound undergoes martensitic transformation [1] and exhibits shape memory behavior at elevated temperatures [2]. The present paper is dedicated to the influence of alloying by Nb and Co along the Ni3 Ta1-x Nbx and Ni3-x Cox Ta cross-sections onto structural and thermodynamic characteristics of phase transformations in Ni3 Ta-based intermetallics. Martensitic transformation in Ni3 Ta intermetallic compound is accompanied by high temperature shape memory effect with complete shape recovery; while Nb and Co alloying additions lead to the deterioration of this effect due to the formation of the orthorhombic equilibrium ( Pmmn ) phase.